First, remove the terms in parenthesis on the right side of the equation being careful to manage the signs of the individual terms correctly:
#4 + 6(x + 2) = 2 - x + 3#
#4 + 6(x + 2) = 2 + 3 - x#
#4 + 6(x + 2) = 5 - x#
Next, eliminate the terms in parenthesis on the left side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis:
#4 + color(red)(6)(x + 2) = 5 - x#
#4 + (color(red)(6) xx x) + (color(red)(6) xx 2) = 5 - x#
#4 + 6x + 12 = 5 - x#
#4 + 12 + 6x = 5 - x#
#16 + 6x = 5 - x#
Then, subtract #color(red)(16)# and add #color(blue)(x)# to each side of the equation to isolate the #x# term while keeping the equation balanced:
#-color(red)(16) + 16 + 6x + color(blue)(x) = -color(red)(16) + 5 - x + color(blue)(x)#
#0 + 6x + color(blue)(1x) = -11 - 0#
#(6 + color(blue)(1))x = -11#
#7x = -11#
Now, divide each side of the equation by #color(red)(7)# to solve for #x# while keeping the equation balanced:
#(7x)/color(red)(7) = -11/color(red)(7)#
#(color(red)(cancel(color(black)(7)))x)/cancel(color(red)(7)) = -11/7#
#x = -11/7#